Os Principios De Economia Substantiva De Karl Polanyi Em Relações De Economia Solidária: O Caso Do Povoado Cruz (currais Novos/Rn) - Gonçalves Silva, Fabiano André; Macedo, Dinara Leslye; Calazans, Silva; González, Juan Miguel Rosa; de Souza, Washington José (Revista Eletrônica de Ciência Administrativa, 2011)
This study focuses economic and social relationships in a fruit culture community under the prism of both principles established by Polanyi (2000) in his work "The Great Transformation" and central assumptions of New Economic Sociology (NES) and Solidarity Economy. The community of Povoado cruz, in the municipality of Currais Novos (Rio Grande do Norte - Brazil), was studied through non-participant observation, and data gathered was analyzed with a qualitative approach. The paper aims at identifying how, and if, social not capitalist relationships, guided by reciprocity, domesticity and redistribution principles, survive within the general capitalist environment. It was observed that, even in predominant market reality, Polanyi and Solidarity Economy principles prevail. Such principles are grounded in values such as solidarity, integration, respect, mutual assistance, cooperation and autonomy. (English)
Administrative Science
Keywords: Brazil; Currais Novos (Brazil); Rio Grande do Norte (Brazil); agroindústria Familiar; domesticidade; domesticity; economia Solidária; family agribusiness; international economic relations; quantitative research; reciprocidade; reciprocity; redistribuição; redistribution; solidarity; solidarity economy

O diferencial do empreendedorismo solidário - Gaiger, Luiz Inácio; da Silva Corrêa, Andressa (The uniqueness of solidarity entrepreneurship., 2011)
The article aims to bring evidence that the solidarity economic undertakings, based on voluntary association, productive cooperation and self-management, employ a unique rationality, different from the capitalistic one. Classical authors such as Schumpeter, Polanyi and Weber, besides some scholars dedicated to the solidarity economy or to micro-entrepreneurship, such as Laville, Portela and Hespanha, give us a theoretical framework, which is used to review the concept of entrepreneurship and to discuss the findings of some empirical investigations, particularly regarding solidarity micro-enterprises. The data base under analysis is provided by the national mapping of the solidarity economy in Brazil and by a qualitative study about small solidarity-based economic experiences, which focused on the relevance of self-management and cooperation, as well as of efficiency and sustainability. Despite their weaknesses and limitations, these experiences reveal the existence of a particular associative kind of entrepreneurship, guided simultaneously by economic and social objectives. This provides convincing empirical arguments for the adoption of a specific approach on entrepreneurship in the context of the solidarity economy and, under certain aspects, in the broader context of small enterprises. (English)
Sustainability Studies
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; WEBER; Max; 1864-1920; associations; institutions - management; associativism; associativismo; economic rationality; entrepreneurship; micro-entrepreneurship; microempreendedorismo; racionalidade econômica; solidarity; solidarity economy; sustainability; works councils

Marketization, social protection and emancipation: ambivalences of feminism in the capitalist crisis - Fraser, Nancy (Revista Direito GV, 2011)
This article is a reflection on the perspectives of feminism in the context of the current crisis of neoliberal capitalism. It is based on the theories of Karl Polanyi that explained the historical process of the crises as a result of the conflict between two elements – marketization and social protection. However, Polanyi Kept out of sight forms of injustice that are not present in the market. He also had the tendency to excuse the social protection as an instrument of domination. This article takes a broader view on the analysis of the conflict between Marketization and social protection. It includes in the analysis a third dimension, the emancipation. The inclusion of this third element transforms the historical process in a three dimensional conflict and forms the heart of a quasi-polanyian perspective that is able to explain the crisis of the XXI century. This text develops this new perspective and uses it to analyze the bets in the emancipation of the gender hierarchy. The triple movement, thus constituted, can overcome the ambivalence of feminism, as the feminist agenda was often manipulated by neoliberalism. The redefinition of social protection in democratic, participatory, non-hierarchic and non-oppressive terms, opens the possibility to a new feminist politics. Keywords: Capitalism; Emancipation; Welfare State; Feminism; Gender.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state